PERAN DPRKPCK PROVINSI JATIM DALAM PENGEMBANGAN FASILITAS PENUNJANG PEMANDIAN AIR PANAS CANGAR - Khovifah Nur Wahyu Agustin; Singgih Manggalou (Halu Oleo University, 2024)
This study aims to see that the development of facilities at the Cangar Hot Springs by Dinas Perumahan Rakyat, Kawasan Permukiman dan Cipta Karya Provinsi Jawa Timur provides a positive contribution to tourist attraction, increasing visitors and locally-generated revenue, while still paying attention to the environmental in conservative areas, and can make regional tourism into national superior tourism. This research uses a descriptive method with a qualitative approach through interview techniques, observation and document study. The research results show that the Dinas Perumahan Rakyat, Kawasan Permukiman dan Cipta Karya Provinsi Jawa Timur carries out five main roles based on Siagian (2012) theory, namely as a stabilizer, innovator, modernizer, pioneer and implementer. As a stabilizer, maintains social stability through monitoring mechanisms involving various parties, although community involvement in planning still needs to be increased. As an innovator, efforts have been made to implement environmentally friendly concepts, but conceptual innovation and work systems need strengthening. As a modernizer, it has succeeded in integrating efficient management, mastery of science, and modern infrastructure to support sustainable tourism. As a pioneer, strategic steps were taken to emphasize social justice, sustainability and environmental care. As an implementer, ensures the construction of facilities according to national standards with an environmentally friendly approach and efficient budget management.